Effect of Using a Mixture of Water Spinach and Brewery Waste to Replace Completed Feed on Performance and Carcasses Quality of Padouhangdam Chickens - Binthavone, Amphaphone; Chitthavong, Malavanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2017)
The aim of the study was to determine the level of water spinach and Brewers’ grains for replacing commercial feed, feed intake and growth performance of padouhungdam chicken and interrogate economies. The experiment was carried out at the poultry farm in Livestock and fishery department, National University. The experiment was arranged in a completely randomized design (CRD) with 3 treatments and 4 replications with average 153 g mean initial live weight. The ingredient of treatments were used difference level of commercial feed, water spinach, brewers’ grains, maize and broken rice. Duration of the experiment were 8 periods (7 days/period) with overall 56 days. The chemical composition of feed was showed: the crude protein of brewers’ grains was highest 27.1% and lowest in broken rice 7.5%. Total feed DM intake (g/day) highest in T1 and lowest in T3 (45.99 and 37.67). The same trended as final live weight highest in T1 and lowest in T3 (1,347g and 1,074.8g). While the average daily gain (ADG) and feed conversion ratio (FCR) were the same as T1 was highest and lowest in T3 for ADG 14.9, 13.3 and 9.9 g/day respectively and FCR were 3.00, 4.27 and 4.60 respectively. There were differences among the diets in the average daily gain (ADG), dry matter intake (DMI), feed conversion ratio (FCR) P<0.05. The Economies of 3 treatments, T1 and T2 were the same cost (133,937 kip, 102,959 kip), T3 lowest 64,233 kip.